The Sexistential Vulnerability of Bodies in Contact in the Philosophy of Jean-Luc Nancy - Francesca Romana Recchia Luciani (Elementa, 2022)
The philosophy of sexual existence as a mode of expression of the “con-being”, pivotal in his book “Sexistence”, occupies a relevant space in Jean-Luc Nancy’s late philosophical production. In this text, the body, the touch, the sex are protrusions that dot a conceptual map that is the result of a long philosophical militancy marked by an authentic “haptic ontology”, a sign of a thought of relationality, interdependence and “sexistencial vulnerability” that connotes the bodies in contact that we all are. But Nancy goes so far as to elaborate a “trans-ontology” through which the “r-existence (resistance) of sexistence” is manifested, that is to say that stubborn rejection of distinct and different bodies to the homologation and uniformity of the identical and of the identity shared by “trans-feminism” which makes its strong point of the inexhaustible combinatorics of the sexes. Thus, both for the sexistencial approach and for the transfeminist one, at the heart of every theory are the lives and practices of distinct and different sexual bodies in relation.